Thirty years of disclosure of conflict of interest in surgery journals - Probst, Pascal; Hüttner, Felix; Klaiber, Ulla; Diener, Markus K.; Büchler, Markus W.; Knebel, Phillip (Surgery, 2015)
Background - A conflict of interest (COI) creates the risk that a professional judgment will be unduly influenced by a secondary interest. In practice, the leading concern is the creation of bias by industry sponsorship. Several organizations for ethics in scientific publishing exist, and standardized disclosure forms have been developed. The aim of this study was to investigate the present status of the definition, management, and disclosure of COI in journals devoted to general and abdominal surgery. - Methods - Information on publisher, definition of COI, whether COI disclosure was mandatory, publication of the disclosure statement with the article, and when publication of disclosure statements was introduced were gathered from instructions for authors and from journal editors and presented descriptively. The hypothesis that journals with a disclosure policy have greater impact factors was tested with a Wilcoxon rank-sum test. - Results - A sample of 64 journals was investigated. In 8 journals (13%) disclosure was deemed unnecessary. In the remaining 56 journals (88%) disclosure of COI was mandatory and in 39 of these journals (61%) the COI statement was published with the article. Journals declaring COI disclosure as mandatory had a greater impact factor (0.626 vs 1.732; P = .006). - Conclusion - Transparency is critical to the reliability of evidence-based medicine. All efforts should be made to give the reader the maximum amount of information. We recommend that every surgeon maintain a standardized, up-to-date disclosure form.
Gesehen am 15.07.2020